2009
DOI: 10.1021/ja903650w
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Alkyne Activation by Frustrated and Classical Lewis Acid/Phosphine Pairs

Abstract: Frustrated and classical Lewis pairs arising from combinations of Lewis acids and phosphines react with terminal alkynes either via C-H activation forming an alkynylborate salt or by addition to alkyne giving a zwitterionic phosphonium borate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
237
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 420 publications
(251 citation statements)
references
References 38 publications
5
237
1
8
Order By: Relevance
“…The first example of an aluminum-based Lewis acid in FLP chemistry was reported in 2009; the strong Lewis acid Al(C 6 F 5 ) 3 , in combination with P t Bu 3 or P(o-tol) 3 , was found to activate the terminal alkyne phenylacetylene, leading to either the deprotonation of the alkyne or the zwitterionic 1,2-addition product (Scheme 7). 43 In both cases, analogous reactivity was previously observed for B(C 6 F 5 ) 3 . Similarly, the FLP Al(C 6 F 5 ) 3 /P t Bu 3 reacts with ethylene generating the 1,2-addition product, whereas reaction with isobutylene results in CH bond activation to afford a phosphonium bis-Al allyl salt (Scheme 7).…”
Section: Overview Of Frustrated Lewis Pairssupporting
confidence: 75%
“…The first example of an aluminum-based Lewis acid in FLP chemistry was reported in 2009; the strong Lewis acid Al(C 6 F 5 ) 3 , in combination with P t Bu 3 or P(o-tol) 3 , was found to activate the terminal alkyne phenylacetylene, leading to either the deprotonation of the alkyne or the zwitterionic 1,2-addition product (Scheme 7). 43 In both cases, analogous reactivity was previously observed for B(C 6 F 5 ) 3 . Similarly, the FLP Al(C 6 F 5 ) 3 /P t Bu 3 reacts with ethylene generating the 1,2-addition product, whereas reaction with isobutylene results in CH bond activation to afford a phosphonium bis-Al allyl salt (Scheme 7).…”
Section: Overview Of Frustrated Lewis Pairssupporting
confidence: 75%
“…It is known from previous publications that FLPs react with terminal alkynes via deprotonative borylation pathway, producing the respective onium alkynylborates 41,42,43,44,45,46 . Indeed, 6 reacts with hex-1-yne giving the respective adduct 31 (Scheme 6).…”
Section: Alkenes Under Hydrogenation Conditionsmentioning
confidence: 99%
“…The same group also showed that some alkenes could undergo C-H bond cleavage using the combination of aluminum compounds and Lewis bases [91]. Terminal alkynes can also be activated by suitable FLPs in a process that is somewhat reminiscent of the copper-assisted deprotonation of alkynes that is at the core of the Sonogashira cross-coupling [25,[92][93]. However, none of these C-H bond cleavage processes could be used for catalytic transformations.…”
Section: C-h Borylation Of Heteroarenes: a Proof Of Conceptmentioning
confidence: 99%